Declarative React : learning React Router 4 (O'Reilly, 2017)
"If you are looking for a best-in-class routing option for React, look no further than React Router 4. It provides a great library for your React or React Native projects with a simple syntax. In this course, we'll explore the basics of Router 4 and apply them to two projects: a React web application and a React Native application. We'll explore the library in detail, covering subjects such as basic routing, linking, code-splitting, animation in routing, and much more. Learners must have JavaScript ES6 standards experience and basic React app development experience."--Resource description page